A Technology Development Matrix for Carbon Capture: Technology Status and R&D Gap Assessment - Baker, Ryan; Alizadeh Sahraei, Ommolbanin; Dal-Cin, Mauro Mario; Bensebaa, Farid (Frontiers in Energy Research, 2022)
Numerous carbon capture, utilization, and storage (CCUS) technologies are under development to reduce CO2 emissions. To evaluate the status of a CCUS technology under development and identify potential gaps for further advancement, we have established a new technology assessment framework and are developing a decision-making tool, the technology development matrix (TDM), starting with available carbon capture technology (CCT) data. TDM is a data inventory system and screening tool. As a screening tool, it can be used for resource allocation decisions in research, development, and deployment (RD&D) by academia, government, and industry. It shares data with techno-economic analysis (TEA) and life-cycle assessment (LCA) tools as an inventory system. By using available data, this TDM framework has been demonstrated on amine-based (monoethanolamine) absorption post-combustion CO2 capture, for pulverized coal (PC) power plant flue gas, as the best available technology (BAT) for comparison. Three groups of promising post-combustion CCTs under development are presented as Alternative Technology (Alt Tech) case studies, including membrane, solid adsorption, and calcium-based chemical looping. By using available data, preliminary analysis enabled technology benchmarking and highlighted knowledge, data, and technology gaps, all providing potential future RD&D focus.